Redox-based epigenetic status in drug addiction: a potential contributor to gene priming and a mechanistic rationale for metabolic intervention - Trivedi, Malav S.; Deth, Richard (Frontiers in Neuroscience, 2015)
Alcohol and other drugs of abuse, including psychostimulants and opioids, can induce epigenetic changes: a contributing factor for drug addiction, tolerance and associated withdrawal symptoms. DNA methylation is the major epigenetic mechanism and it is one of more than 200 methylation reactions supported by methyl donor S-adenosylmethionine (SAM). The levels of SAM are controlled by cellular redox status via the folate and vitamin B12-dependent enzyme methionine synthase (MS), for example; under oxidative conditions MS is inhibited, diverting its substrate homocysteine (HCY) to the transsulfuration pathway. Alcohol, dopamine and morphine, can alter intracellular levels of glutathione (GSH)-based cellular redox status, subsequently affecting S-adenosylmethionine (SAM) levels and DNA methylation status. In this discussion, we compile this and other existing evidence in a coherent manner to present a novel hypothesis implicating the involvement of redox-based epigenetic changes in drug addiction. Next, we also discuss how “gene priming” phenomenon can contribute to maintenance of redox and methylation status homeostasis under various stimuli including drugs of abuse. Lastly, based on our hypothesis and some preliminary evidence, we discuss a mechanistic explanation for use of metabolic interventions / redox-replenishers as symptomatic treatment of alcohol addiction and associated withdrawal symptoms. Hence, the current review article strengthens the hypothesis that neuronal metabolism has a critical bidirectional coupling with epigenetic changes in drug addiction and we support this claim via exemplifying the link between redox-based metabolic changes and resultant epigenetic consequences under the effect of drugs of abuse.